Freedom as the Governing Principle of Democracy in Farrokhi Yazdi's Thought - soroush alizade; ahmad khosravi (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
The present paper examines the concept of freedom and its different categories, and more specifically, the freedom of speech in the poetry of Farrokhi Yazdi from a legal perspective. According to this view, freedom is tied up with the concept of "having a right to" and it is defined as an absence of obstacles and limitations. Freedom, similar to justice and public order, is an abstract concept which has been debated and interpreted differently from the perspective of different sciences. On the one hand, freedom has been established as one of the governing principles of democracy, and on the other hand, it has occupied a high position in literary expressions, especially, in poetry. Naturally, an individual would oppose a view which seeks to crucify one's fundamental rights, and freedom is considered as one of these rights because it turns a human being into a subject. In Iran, the beginning of some aspects of such confrontational views can be found in the Constitutional Era. Thus, the thinkers of this era, also influenced by this view, tried to prove the existence of the concept of freedom as a right. Farrokhi Yazdi was one of such thinkers who was at the heart of this conflict. Even though he did not directly address the concept of freedom and its necessity for democracy in his poems, his goal was to achieve a kind of democracy the materialization of which depended on achieving the types of freedom which, in various documents, are considered among fundamental human freedoms today. Now the question is, what kinds of freedom does Farrokhi Yazdi mean by freedom? To find the answer, we draw on a descriptive and analytical method and tie the research to the law and legal matters.